Pengembangan Sistem Informasi Manajemen Persediaan Barang berbasis Web (Studi Kasus: BYW Studio) - Reinata Devi Nindya Tirzasari; Issa Arwani; Buce Trias Hanggara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Blossom Your Way (BYW) Studio is a small business engaged in selling K-POP fanmade merchandise. The types of goods managed are divided into two, namely raw goods and ready-to-sell finished goods. Management of ready-to-sell finished goods inventory has taken advantage of the features provided by the marketplace, but for the management of raw goods it still uses manual recording into a book. During this manual management of raw goods inventory, there are problems that arise, namely they often run out of stock of raw goods suddenly when there is a surge in orders that occur during the Marketplace Event. This has an impact on store performance in the marketplace as well as an increase in order cancellations due to delays in packaging and delivery. From the results of the analysis of these problems, a web-based inventory management information system was developed by utilizing the integration of the Telegram Bot API service as a medium for sending real-time notification of the remaining stock of raw goods 5 after a reduction in the amount of stock. The Waterfall method is used in the development of this system, as well as using the Laravel framework. The database is implemented using MySQL. The system is tested using compatibility testing and validation testing. The results of the validation testing using the black-box method produce a 100% valid percentage. And the results of compatibility testing using the Sortsite application show that the developed system can run well on several browsers.